Phytotherapy in India: transition of tradition to technology - S. Babu, Lazar Mathew and (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The disease preventive and health promoting approach based on herbal medicine takes into consideration, the promotion of health and treating ailments is holistic way and finds increasing acceptability in many regions of the world, India and China being in the forefront. The practice of herbal medicine basically depends on folklore and by experiences of people over a long period of time. However, very little research especially in the area of basic science has been conducted in a systematic manner. Medicinal plants with a long history of safe and effective use are likely to have a pharmaceutical effect. The use of plants in traditional medicine can be explained by physiologically active phytochemical compounds of a species and also by its ascribed meaning in a culture.Ã‚Â Plants produce a great diversity of substances that could be of therapeutic significance in many areas of medicine. However, the chemical nature of plant compounds present naturally as such and in extract, is puzzling. It is important to know constituents of plant extracts and their relative importance in their therapeutic value. The alkaloids and other compounds are characterized and tested for their medicinal value from these plants which include not only the unexplored tribal plants but also the spices, condiments and vegetables which are already in use. In last decade, there is a renewed interest in the development of herbal drugs underlined by the understanding of mechanism of action rather than based on faith and folk, as it happened in past. Several aspects on integrated approaches of drug development from herbs have explored many potential lead phytochemicals. Nonetheless, even the limited number of mechanistic experiments reveals that numerous mechanisms are likely involved in the various actions of even a single herbal medicine. It will be the elucidation of such mechanisms that will provide the scientific basis for establishing the efficacy and safety of not only Chinese and Indian herbal medicines but all forms of medicinal botanicals.